2022
DOI: 10.1002/cre2.554
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pulse duration and water/air cooling ratio on the efficiency of Er:YAG 2940 nm laser in debonding of porcelain laminate veneers: An in vitro study

Abstract: Objective: To determine the effectiveness of different pulse durations (PD) and the water/air (W/A) cooling ratio of the Er:YAG 2940 nm laser that are required for debonding porcelain laminate veneers (PLV), by investigation of the needed time for PLV debonding (DT) and the changes in dental pulp temperature.Materials and Methods: Thirty-six extracted noncarious human maxillary premolars were prepared for receiving PLV. Samples were randomly assigned to six different groups, based on PD and the W/A ratio: Grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Our pulse duration was set to 50 µs. Shorter pulse durations were according to AlBalkhi et al more efficient in debonding of veneeres with an Er:YAG laser [28]. Abdel Sadek et al reported on the rebonding of laser debonded lithiumdisilicate and zirconiumoxide ceramics and found lower bonding strength [29].…”
Section: Discussionmentioning
confidence: 99%
“…Our pulse duration was set to 50 µs. Shorter pulse durations were according to AlBalkhi et al more efficient in debonding of veneeres with an Er:YAG laser [28]. Abdel Sadek et al reported on the rebonding of laser debonded lithiumdisilicate and zirconiumoxide ceramics and found lower bonding strength [29].…”
Section: Discussionmentioning
confidence: 99%
“…Although a considerable number of studies on laminate veneer debonding with Er:YAG lasers have been published [18][19][20][21], there are a limited number of studies on full-coverage all-ceramic crown debonding and removal [7,17,22]. Except for clinical reports and non-evidence-based trials, the appropriate laser application parameters for Er:YAG laser debonding of a full-coverage all-ceramic restoration in different thicknesses luted on premolars have not yet been documented.…”
Section: Discussionmentioning
confidence: 99%
“…According to Albalkhi et al [20] the debonding time and temperature change were affected by the pulse duration (PD) and water/air (W/A) cooling ratio. It was reported that laminate veneers were successfully debonded when the pulse duration was SSP (50 µs) or MSP (100 µs), which are efficient, fast, and safe parameters for the removal of lithium disilicate veneers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation